Political Participation in Ghana’s Fourth Republic: The Role of Women’s Wings of Political Parties - Yusif, A. (University of Ghana, 2018)
Globally, there has been a huge outcry on the need to enhance women political participation because women have been marginalized for far too long. In this regard, gender inequality in all sphere of our society has received international attention and acceptance. For many years, women and other feminists’ groups have fought hard to create room for equal participation of both men and women in the political arena. Their effort has come with a marginal improvement of women’s participation due to entrenched patriarchal nature of the political arena. Samuel Huntington’s “third wave” of democratization in the early 1990s has seen a new political opening in Africa and elsewhere in the world. In Ghana, this re-birth of democracy has led to the demise of authoritarian rule where women’s political activities have been re-hatched and enhanced. Ghana’s Fourth Republic has provided a fertile political space for women political participation. In response to this, political parties have restructured their parties to create women’s wings. This study sets out with the objective of finding out what role these women’s wings of the political parties play. The study was conducted in the Greater Accra Region and Accra Metropolitan Assembly (AMA). It is a qualitative study and used in-depth interview to collect data from 24 respondents comprising constituency, regional and national women organizers of NPP and NDC. Purposive sampling technique was used to sample respondents. Purposive sampling was chosen because information can only be gotten from these specific group of people whiles Qualitative Content Analysis was used to analyze the data collected from respondents. The study found that the main mandate of the women’s wings of the political parties is to organize women at the grassroots and to canvass women votes for their parties. They serve as campaign tools for the parties. The women’s wings also use their platform to advance women’s interests and their welfare. Their activities range from economic, social and political. It was also discovered that the women’ wings serve as an avenue for political participation and recruitment, a platform to influence gender policies and advance the course of women. The main challenges the women’s wings face are inadequate allocation of funds and male dominance in the parties’ affairs. Others include total neglect of the women’s wings, especially when the party is out of power as the activities of women’s wings usually become dormant. Additionally, jealousy, backbiting, and hatred among the women themselves were also identified. The findings of this study will be of great interest to political parties particularly women’s wings. As a limitation, the findings of this study may not be applicable to other regions and districts in Ghana because of economic, social, cultural, religious and demographic differences.
MPhil.
Keywords: Political Participation; Ghana’s Fourth Republic; Women’s Wings; Political Parties